2020
DOI: 10.21203/rs.2.11227/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tuberculosis Treatment Outcomes: A Fifteen Year Retrospective Study In Jos North And Mangu, Plateau State, North - Central Nigeria

Abstract: Background: Globally, tuberculosis (TB) is the leading cause of death from a single infectious agent. Adherence to TB therapy is an important factor in treatment outcomes, which is a critical indicator for evaluating TB treatment programs. This study assessed TB treatment outcomes using a fifteen-year record of tuberculosis patients who received treatment in Jos North and Mangu Local Government Areas of Plateau State Nigeria. Methods: The retrospective facility based study was done in five TB treatment centers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
3
1
1
1
Order By: Relevance
“…However, the DOTS strategy is being challenged by many issues such as poor adherence, treatment default and failure (7,8). In this study, the finding of treatment success rate of 61.5% in the TB patients on treatment is similar to the report from another facility in north-central Nigeria which reported 67% of TB patients had successful treatment outcomes (10). Similar findings were also reported in other studies from East Africa with rates of successful treatment outcomes between 60% and 67% (12,13).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the DOTS strategy is being challenged by many issues such as poor adherence, treatment default and failure (7,8). In this study, the finding of treatment success rate of 61.5% in the TB patients on treatment is similar to the report from another facility in north-central Nigeria which reported 67% of TB patients had successful treatment outcomes (10). Similar findings were also reported in other studies from East Africa with rates of successful treatment outcomes between 60% and 67% (12,13).…”
Section: Discussionsupporting
confidence: 90%
“…The low transfer out rate of 2.3% in our study may be a further testament to this. The high rate of death (7.8%) among TB patients in our study is similar to the report of a study from Jos, northcentral Nigeria (10), but lower than the death rates reported in studies from southern Nigeria by Bamidele et al, (11) and Umeokonkwo et al, (16). How-ever, the rate in our study is higher than those reported from other regions of Africa and Europe (12,17).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…MOÇAMBIQUE, 2018.2.3.4 Fatores Associados ao Desfecho do Tratamento da TuberculoseEstudos têm mostrado que o alcance do tratamento bem-sucedido da TB depende em grande medida da combinação correta entre a condição clínica do paciente, regime terapêutico escolhido, cumprimento efetivo e a toma correta dos medicamentos durante o período definido. Portanto, nem sempre este desiderato é alcançado, pois não menos frequente regista-se desfechos desfavoráveis como a morte, falência terapêutica e abandono.Alguns fatores relacionados às características sociodemográficas, clínico-epidemiológicas dos doentes de TB e aos sistemas de saúde têm sidos identificados como de importância fundamental no processo do tratamento da doença(ANYANTI et al, 2020;DOS SANTOS et al, 2012 apud MS- Brasil, 2005.da doença e pela razão contrária estima-se que cerca de 64% de casos podem ter desfechos não favoráveis(SARIEM et al, 2020) como longos períodos de infecção, resistência aos medicamentos e a morte (TSEGAW e YIMER, 2018).Pela importância epidemiológica que a aderência ao tratamento representa no controle de doenças, esforços têm vindo a ser empreendidos no sentido de identificar as potenciais causas associadas à ocorrência contrária. Por exemplo, com base em um estudo randomizado envolvendo 234 novos casos de TB com aplicação de um questionário estruturado, T. S. BAM, et al(2006), identificaram que a provisão de informação diária sobre a importância de DOTS nos centros de atendimento de pacientes de TB influenciou significativamente para o sucesso (OR 6.27, 95%CI 2.88-13.64).Paralelamente, A. TRAJMAN et al, (2010) identificaram por meio de um estudo clínico randomizado que regimes curtos (4 meses) e baixas doses de medicamentos influenciaram para o sucesso na aderência ao tratamento nos primeiros meses de seguimento clínico.…”
unclassified